Novel Neurotransmitter and Receptors: An Overview - Aggarwal, Juhi; Modi, Mansi (Recent Developments in Chemistry and Biochemistry Research Vol. 4, 2024)
The nervous system's intricate network relies on neurotransmitters and receptors for signal transmission, orchestrating complex physiological and behavioural responses. While classical neurotransmitter systems have been extensively studied, recent research has unveiled novel neurotransmitters and receptors, expanding our understanding of neural communication. This overview provides a comprehensive synthesis of both classic and emerging neurotransmitter-receptor systems, delineating their functions and receptor subtypes. Additionally, it highlights recent discoveries in the field, emphasizing the role of advanced techniques in identifying previously unknown signalling molecules. By elucidating the intricate landscape of neurotransmitter-receptor interactions, this overview underscores the importance of ongoing research in shaping our understanding of brain function and informing therapeutic interventions for neurological and psychiatric disorders.